The sociology of early childhood : critical perspectives - Gabriel, Norman (Los Angeles : Sage, 2017)
Introducing readers to the key historical and sociological perspectives on childhood, this book includes discussion features to encourage students to be critical and discursive around the subject.
Historical and sociological perspectives on childhood -- A relational sociology of early childhood -- Growing up beside you-social habitus in early childhood -- Young children's play-challenging the adult establishment -- Civilising young children-long-term parenting trends -- New media technologies and the sexualisation of childhood.
Includes bibliographical references and index.
Keywords: Early childhood education -- Social aspects